Comparative evaluation of newly developed model-based and commercially available hybrid-type iterative reconstruction methods and filter back projection method in terms of accuracy of computer-aided volumetry (CADv) for low-dose CT protocols in phantom study. Issue 8 (August 2016) - Ohno, Yoshiharu; Yaguchi, Atsushi; Okazaki, Tomoya; Aoyagi, Kota; Yamagata, Hitoshi; Sugihara, Naoki; Koyama, Hisanobu; Yoshikawa, Takeshi; Sugimura, Kazuro
Abstract: Purpose: To directly compare the capability of three reconstruction methods using, respectively, forward projected model-based iterative reconstruction (FIRST), adaptive iterative dose reduction using three dimensional processing (AIDR 3D) and filter back projection (FBP) for radiation dose reduction and accuracy of computer-aided volumetry (CADv) measurements on chest CT examination in a phantom study. Materials and methods: An anthropomorphic thoracic phantom with 30 simulated nodules of three density types (100, −630, and −800 HU) and five different diameters was scanned with an area-detector CT at tube currents of 270, 200, 120, 80, 40, 20, and 10 mA. Each scanned data set was reconstructed as thin-section CT with three methods, and all simulated nodules were measured with CADv software. For comparison of the capability for CADv at each tube current, Tukey's HSD test was used to compare the percentage of absolute measurement errors for all three reconstruction methods. Absolute percentage measurement errors were then compared by means of Dunett's test for each tube current at 270 mA (standard tube current). Results: Mean absolute measurement errors of AIDR 3D and FIRST methods for each nodule type were significantly lower than those of the FBP method at 20 mA and 10 mA (p < 0.05). In addition, absolute measurement errors of the FBP method at 20 mA and 10 mA was significantly higher than that at 270 mA for all nodule types (p < 0.05). Conclusion: The FIRST and AIDR 3D methods are more effective than the FBP method for radiation dose reduction, while yielding better measurement accuracy of CADv for chest CT examination.